2019
DOI: 10.7717/peerj.6344
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases to induce the expression of genes associated with apoptosis during corpus luteum development in bovine

Abstract: Here we investigated the expressions of apoptosis-associated genes known to induce programed cell death through mRNA expressions of two matrix metalloproteinases (MMPs) that are involved in the degradation of collagen and basal membrane in luteal cells cultured in the treatment media. Our results show that the activity of MMP-2 gelatinase was higher in the CL2 and CL1 of luteal phase, was gradually decreased in the CH2 and CH3 of luteal phase. In particular, the expressions of P4-r and survival-associated gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We therefore speculated that UPR may be involved in the process of goat luteal cells dividing from follicular granulosa cells and theca cells. The regression of the CL occurs in the late luteal phase of the goat CL and is accompanied with the apoptosis of the luteal cells stimulated by PGF2α (Tanaka et al, 2000;Diaz et al, 2002;Luttgenau et al, 2016;Kim et al, 2019). A previous study revealed that the caspase-dependent apoptosis pathway was significantly activated in bovine CL after PGF2α-injection (Kliem et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…We therefore speculated that UPR may be involved in the process of goat luteal cells dividing from follicular granulosa cells and theca cells. The regression of the CL occurs in the late luteal phase of the goat CL and is accompanied with the apoptosis of the luteal cells stimulated by PGF2α (Tanaka et al, 2000;Diaz et al, 2002;Luttgenau et al, 2016;Kim et al, 2019). A previous study revealed that the caspase-dependent apoptosis pathway was significantly activated in bovine CL after PGF2α-injection (Kliem et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Structural changes in the corpus luteum can be observed in the rapid reorganisation of tissues during the process of a mammal becoming fertile during the oestrous cycle. In the process of tissue reorganisation, functional changes involve cytoplasmic reorganisation and changes in the role of cells the apoptosis mechanism (14). However, the main functional changes in cells can be observed simultaneously in apoptosis and cytoplasmic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of LH and the difference in expression of 20α-HSD may have a certain influence on cell reorganisation because of the difference in expression of MMPs and TIMPs. However, it is not known whether these differences regulate the two processes of apoptosis (13,14,16). The regulation of autophagy has not yet been elucidated, and further studies are needed to understand the interaction of several components (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remodeling process involves the production and activation of various ECM-degrading enzymes, such as matrix metalloproteinases (MMPs). These enzymes facilitate the breakdown of the ECM and contribute to luteal cell apoptosis [81]. Additionally, cytokines and chemokines released by immune cells can modulate this [82].…”
Section: Extracellular Factorsmentioning
confidence: 99%